Gender in Peacebuilding Local Practices in Indonesia and Nigeria - Prügl, Elisabeth; Rigual, Christelle; Kunz, Rahel; Achakpa, Mimidoo; Myrttinen, Henri; Onyesoh, Joy; Rahmawati, Arifah; Udasmoro, Wening (International Development Policy, 2021)
This volume analyses how and to what effect gender shapes, and is shaped by, peacebuilding initiatives in relation to other social dynamics in the context of local peacebuilding initiatives in Indonesia and Nigeria.; Readership: Academic scholars and researchers, policymakers and development practitioners interested in international development policy, peacebuilding and gender and their effects on development, economic and political trends, and local development issues.